Effect of low power laser irradiation on the viscosity and the hydrogen ion concentration (pH) of bio liquids in vitro - Ayman A. Ahmmed; Tymaa Alglami (College of Education for Pure Sciences, 2012)
Abstract: The effect of He-Ne laser irradiation at the wave length 632.8 nm on the viscosity and hydrogen ion concentration (pH) of normal blood and ringer solution were studied in vitro. The result of the study showed that 3mW laser irradiation of 5 mm spot diameter reduced the viscosity and increased the hydrogen ion concentration (pH) of irradiated blood and ringer solution samples as compared to the un irradiated control value and this change was obvious at 90 minutes of exposure. Thus, the effect of He-Ne laser irradiation depends on irradiation duration.